Results of modern radiation-hygienic surveys of settlements of Bryansk Oblast of the Russian Federation bordering the Republic of Belarus. Part 3: Radionuclide content in agricultural food products - I. K. Romanovich; A. B. Bazyukin; A. A. Bratilova; G. Ya. Bruk; E. A. Drozdova; T. V. Zhesko; M. V. Kaduka; O. S. Kravtsova (Радиационная гигиена)
The third article in a series of publications devoted to the results of studying the current radiation situation in the territories of the Bryansk region bordering the Republic of Belarus presents results of studies of the content  of  radionuclides  (137Cs  and 90Sr)  in  samples  of  agricultural  food  products  produced  in  the  personal subsidiary plots of the population. The regularities of changing 137Cs and 90Sr content in samples of cow’s milk and potatoes depending on the level of radioactive contamination of the territory were studied; the present values of the quantities characterizing the distribution of the ratio of the activity concentration of radionuclides in agricultural food products to the density of radioactive contamination of the soil of the territory were deter -mined. The ratios of average values of 137Cs activity concentration in milk from stalled and grazing periods for cattle were analyzed. The results of the study show that some dairy product samples (less than 1%) do not meet the radiological safety criterion. Exceedances of the hygienic standards were not found in the studied samples of potatoes, vegetables, and meat of farm animals.